2000
DOI: 10.1128/jcm.38.9.3492-3494.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Expression, and Antigenicity of Seto Virus Belonging to Genogroup I Norwalk-Like Viruses

Abstract: The viral capsid protein of the Seto virus (SeV), a Japanese strain of genogroup I Norwalk-like viruses (NLVs), was expressed as virus-like particles using a baculovirus expression system. An antigen detection enzyme-linked immunosorbent assay based on hyperimmune antisera to recombinant SeV was highly specific to homologous SeV-like strains but not heterologous strains in stools, allowing us type-specific detection of NLVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It was specific only for GII/4 strains, which were used as an immunogen that showed high sensitivity and specificity against GII/4 strains. This kind of reactivity has been observed in many laboratories, as it is specific only for genetic subgroups used for immunization [Hale et al, 1999;Kobayashi et al, 2000;Kamata et al, 2005]. In a recent report, however, the GII/1 polyclonal antibody cross-reacting strongly with other GII genotypes, and the GI/11 polyclonal antibody cross-reacting strongly with both GI and GII genotypes were obtained, and they showed the possibility of detecting a broadrange of genotypes in clinical specimens .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was specific only for GII/4 strains, which were used as an immunogen that showed high sensitivity and specificity against GII/4 strains. This kind of reactivity has been observed in many laboratories, as it is specific only for genetic subgroups used for immunization [Hale et al, 1999;Kobayashi et al, 2000;Kamata et al, 2005]. In a recent report, however, the GII/1 polyclonal antibody cross-reacting strongly with other GII genotypes, and the GI/11 polyclonal antibody cross-reacting strongly with both GI and GII genotypes were obtained, and they showed the possibility of detecting a broadrange of genotypes in clinical specimens .…”
Section: Discussionmentioning
confidence: 88%
“…Those MAbs were broadly reactive, recognizing GI or GII, or both GI and GII [White et al, 1997;Yoda et al, 2003;Parker et al, 2005]. On the other hand, the rabbit anti-VLP PolyAbs were highly specific for genotypes used as immunogens, especially when used in the antigen-ELISA [Hale et al, 1999;Kobayashi et al, 2000;Kamata et al, 2005]. A recent report revealed that some polyclonal antisera showed broadrange cross-reactivity: GI/11 antiserum cross-reacted strongly, not only with GI genotypes, but also GII genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The animals were bled 1 week after the last booster injection. The antibody titers of rabbit hyperimmune sera to VLPs were tested in parallel by an indirect ELISA, as described previously for rSeto 124 VLPs [Kobayashi et al, 2000b] except that a VLP concentration of 0.5 mg/ ml was used to coat the ELISA plate. ELISA titers were expressed as the reciprocal of the highest dilution of antiserum giving an optical density (OD) at 450 nm of >0.2.…”
Section: Hyperimmune Seramentioning
confidence: 99%
“…An antigen detection ELISA was developed using the rabbit hyperimmune sera to four recombinant capsid proteins (r645, r809, r754, and r10-25), and three previously characterized VLPs, Seto 124 VLPs (rSeto) [Kobayashi et al, 2000b], Chiba 407 VLPs (rChiba) [Kobayashi et al, 2000a], and Chitta 1876 VLPs (rChitta) [Kobayashi et al, 2000c]. Microtiter plates (96-well) (Maxisorp, Nunc, Denmark) were coated with 100 ml (0.5 mg of IgG/ml) of the rabbit preimmune (1:8,800 dilution) or hyperimmune sera (1:8,800-12,000 dilutions) in a coating buffer (0.05M carbonate-bicarbonate buffer, pH 9.6) overnight at 48C.…”
Section: Antigen Elisamentioning
confidence: 99%
“…Among the different parts of the genome, the coat protein sequences offer the best choice in computation-based strain prediction methods in caliciviruses, mainly because, of their highest overall variability and antigenic correlations as compared with sequences of the other genomic regions. This is true even for the human caliciviruses for which antigenic relationships are often deduced on the basis of antigen and antibody ELISAs using expressed capsid proteins as has been done for noroviruses [ 21 , 37 - 39 ]. We examine here a computational approach to predict strains in both picornaviruses and caliciviruses on the basis of capsid sequences.…”
Section: Introductionmentioning
confidence: 99%